Information about Electronic Governance: A Tool to Curb Corruption in Nigeria - Jimoh, Rasheed Gbenga; Longe, O. B.; N., Ndunagu J. (Jurnal The Messenger, 2018)
Corruption has been declared to be the cause of poverty and poor standard of living in the Nigeria. This is caused by lack of accountability and transparency in the Government sector, mostly aided by manual accounting system and ordinary paper document in the operation of the sector. Sequel to the evolution of Information and Communication Technology, electronics governance was implemented in Nigeria. Therefore, this study examines the role of electronic governance as a tool for curbing corruption in Nigeria. As such, a survey instrument were administered to 240 civil servants from different public sectors in Nigeria. The findings revealed that, implementation of e-governance has helped to curb corruption in Nigeria and also played a great role in improving efficiency of Nigeria economy. Also this study found that, the need to embrace electronics governance given the phobia exhibited by many Nigerian populace and workforce as to the use of electronics governance.